FEATURES OF GROWING AND STORAGE OF SEED COLLECTION OF THE GENE POOL OF VEGETABLE CROPS. - O. N. Shabetya (Овощи России, 2015)
The features  of cultivation and storage  of seed collections of the gene pool of vegetable crops have been studied. Elements to improve growing techniques  of seeds  for dispatch for long term storage  are offered. The optimal conditions for storage  of vegetable seeds  of the gene bank are found. The features of conservation of the collection of vegetative propagated  vegetable crops have been analyzed.